(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This scientific article comprehensively analyzes the formation, development, and modern clinical significance of Latin terminology in traumatology and orthopedics. The study evaluates the role of Latin language in anatomical nomenclature, classification of traumatic injuries, clinical diagnostics, and international medical communication. Particular attention is paid to the linguistic, morphological, and semantic characteristics of Latin terms widely used in traumatology. The findings demonstrate that Latin remains the fundamental basis of terminological standardization in modern traumatology. The study also confirms that advanced teaching of Latin terminology in medical education contributes significantly to the professional competence of future traumatologists and orthopedic specialists.